Neurodynamics of executive control processes in bilinguals: evidence from ERP and source reconstruction analyses - Heidlmayr, Karin; Hemforth, Barbara; Moutier, Sylvain; Isel, Frédéric (Frontiers in Psychology, 2015)
The present study was designed to examine the impact of bilingualism on the neuronal activity in different executive control processes namely conflict monitoring, control implementation (i.e. interference suppression and conflict resolution) and overcoming of inhibition. Twenty-two highly proficient but non-balanced successive French-German bilingual adults and 22 monolingual adults performed a combined Stroop/Negative priming task while event-related potential (ERP) were recorded online. The data revealed that the ERP effects were reduced in bilinguals in comparison to monolinguals but only in the Stroop task and limited to the N400 and the sustained fronto-central negative-going potential time windows. This result suggests that bilingualism may impact the process of control implementation rather than the process of conflict monitoring (N200). Critically, our study revealed a differential time course of the involvement of the anterior cingulate cortex (ACC) and the prefrontal cortex (PFC) in conflict processing. While the ACC showed major activation in the early time windows (N200 and N400) but not in the latest time window (late sustained negative-going potential), the PFC became unilaterally active in the left hemisphere in the N400 and the late sustained negative-going potential time windows. Taken together, the present EEG data lend support to a cascading neurophysiological model of executive control processes, in which ACC and PFC may play a determining role.